2004
DOI: 10.1074/jbc.m402037200
|View full text |Cite|
|
Sign up to set email alerts
|

Myocardial Cell Death and Regeneration during Progression of Cardiac Hypertrophy to Heart Failure

Abstract: Cardiac hypertrophy and ensuing heart failure are among the most common causes of mortality worldwide, yet the triggering mechanisms for progression of hypertrophy to failure are not fully understood. Tissue homeostasis depends on proper relationships between cell proliferation, differentiation, and death and any imbalance between them results in compromised cardiac function. Recently, we developed a transgenic (Tg) mouse model that overexpress myotrophin (a 12-kDa protein that stimulates myocyte growth) in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
0
36
0
2
Order By: Relevance
“…load is known to activate signaling cascades, including oxidative stress, which in turn predisposes to cardiomyocyte apoptosis (22), and the latter is seen during the transition from hypertrophy to dilated cardiomyopathy (23). In wild-type mice 12 weeks after transverse aortic banding we found a ϳ1.8-fold decrease in ARC levels on Western blot compared with sham-operated mice, and this decrease in ARC protein levels was associated with a marked increase in MDM2 expression (Fig.…”
Section: Increased Mdm2 Expression Is Associated With Decreased Arc Pmentioning
confidence: 68%
“…load is known to activate signaling cascades, including oxidative stress, which in turn predisposes to cardiomyocyte apoptosis (22), and the latter is seen during the transition from hypertrophy to dilated cardiomyopathy (23). In wild-type mice 12 weeks after transverse aortic banding we found a ϳ1.8-fold decrease in ARC levels on Western blot compared with sham-operated mice, and this decrease in ARC protein levels was associated with a marked increase in MDM2 expression (Fig.…”
Section: Increased Mdm2 Expression Is Associated With Decreased Arc Pmentioning
confidence: 68%
“…Additionally, our results suggest that endocardial endothelial cell resistance to apoptosis is possibly linked to the ability of these cells to regulate programmed cell death at very early stages of apoptotic process, the loss of mitochondrial transmembrane potential (MMP). Previous studies have reported the importance of both caspase-dependent and caspaseindependent cell death in cardiovascular dysfunction [26][27][28][29][30][31]. Since endocardial endothelial cells appear to have resistance to transmembrane potential loss, both caspasedependent and independent death signaling are likely to be inhibited in these cells.…”
Section: Discussionmentioning
confidence: 98%
“…Both FasR and FasL have been identified in lymphoid [23] and epithelial cells. Expression FasR has been demonstrated in renal tubules [24], skeletal muscle [25], smooth and cardiac muscle [26,27], pituitary gland [28], parathyroid gland [29], pancreatic islets [30], hepatocytes [31], testicular germ cells [32], prostatic glands [33], neurons [34], epithelium of fallopian tube [29,35], endometrial glands [29,35], trophoblasts [29,35], bronchial epithelial [29,35] and gastrointestinal-type cells [29,35], chondrocytes [36], thyroid cells [37], and skin [38].…”
Section: Discussionmentioning
confidence: 98%